ANTIOXIDANT AND ANTI-INFLAMMATORY EFFECTS OF CURCUMIN CONTRIBUTE INTO ATTENUATION OF ACUTE GENTAMICIN-INDUCED NEPHROTOXICITY IN RATS - AL-KURAISHY, HAYDER M; AL-GAREEB, ALI I; RASHEED, HUDA ABDULBAKI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Nephrotoxicity is a renal-specific situation in which the excretion of toxic metabolites is reduced due to toxic agents and drugs. Gentamicin is an antibiotic belongs to aminoglycoside group which may induce nephrotoxicity due to induction of oxidative stress. Curcumin is a component of traditional medicine with significant nephroprotective effect. Therefore, the objective of the present study was to evaluate the nephroprotective effect of curcumin on gentamicin-induced nephrotoxicity. Methods: A total of 30 male Sprague-Dawley rats were used which divided into Group 1 (n=10): Rats treated with distilled water 5 ml/kg plus normal saline 5 ml/kg for 12 days, Group 2 (n=10): Rats treated with distilled water 5 ml/kg plus gentamicin 100 mg/kg for 12 days, and Group 3 (n=10): Rats treated with curcumin 100 mg/kg plus gentamicin 100 mg/kg for 12 days. Blood urea, serum creatinine, malondialdehyde (MDA), kidney injury molecule (KIM-1), and cystatin-C were measured in both control and experimental groups. Results: Rats treated with gentamicin showed nephrotoxicity as evident by significant elevation in blood urea, serum creatinine, KIM-1, MDA, and cystatin-C sera levels. Curcumin leads to significant reduction of blood urea and serum creatinine compared to gentamicin group, p<0.05. Curcumin also reduced MDA, KIM-1, and cystatin-C sera levels significantly compared to gentamicin group, p<0.01. Conclusion: Curcumin produced significant nephroprotective effect on gentamicin-induced nephrotoxicity through modulation of oxidative stress and inflammatory biomarkers.